수정된 목표지향 행동모델을 적용한 스포츠 O2O 서비스 잠재 이용자의 수용 의도 예측 - 이지현; Jihyun Lee; 김태중; Taejung Kim; 조광민; Kwang Min Cho (Ch'eyuk kwahak yŏn'gu, 2018)
[목적] 이 연구는 수정된 목표지향 행동모델을 적용하여 스포츠 O2O 서비스 잠재 이용자의 수용 의도를 예측하는데 목적이 있다. [방법] 연구 방법으로는 총 330부의 스포츠 O2O 서비스 이용 경험이 없는 잠재 이용자들에게 설문지를 배포하고 편의 표본추출법(convenience sampling)에 의해 표집 하였다. 총 330부의 설문지 중 평소 생활 체육에 참여하지 않거나 불성실한 응답자를 제외한 총 288부가 최종 분석에 사용되었다. 본 연구에서 자료처리방법은 SPSS23.0과 AMOS22.0을 이용하여 분석을 실시하였다. [결과] 그 결과 첫째, 스포츠 O2O 서비스 잠재 이용자들의 태도와 주관적 규범은 열망에 긍정적인 영향을 미치는 것으로 나타났다. 둘째, 스포츠 O2O 서비스 잠재 이용자들의 인지된 행동통제는 열망에 긍정적인 영향을 미치지 않는 것으로 나타난 반면 인지된 행동통제는 수용의도에 긍정적인 영향을 미치는 것으로 나타났다. 셋째, 스포츠 O2O 서비스 잠재 이용자들의 긍정적인 예기정서는 열망에 긍정적인 영향을 미치는 것으로 나타났다. 하지만 부정적인 예기정서는 열망에 긍정적인 영향을 미치지 않는 것으로 나타났다. 넷째, 스포츠 O2O 서비스 잠재 이용자들의 열망은 수용의도에 긍정적인 영향을 미치는 것으로 나타났다. [결론] 본 연구의 결과를 토대로 수용 의도를 예측함에 있어 태도 및 주관적 규범, 긍정적 예기정서가 열망에 그리고 열망은 수용의도에 영향을 미치는 것처럼 스포츠 O2O 서비스 잠재 이용자들을 이끌 수 있는 열망이라는 요인의 향상을 이끌어 낼 수 있는 마케팅을 하는 것이 효과적이라는 것을 시사한다. [Purpose] The purpose of this study was to examine acceptance intentions of Sports O2O Service Potential consumers using the revised model of goal-directed behavior. [Methods] The 330 surveys were distributed to potential consumers through convenience sampling method for pilot study. Due to the reliability of data, 42 samples were discarded and 288 samples were put to actual analysis. Then data were analyzed for frequency analysis, reliability analysis, correlation analysis and structural equation modeling technique via SPSS 23.0 and AMOS 22.0. [Results] The results of this study were as follows. First, attitude and subjective norm had a positive effect on desire. Second, perceived behavior control did not affect on desire but had a positive affect on acceptance intention. Third, positive anticipated emotions had a positive effect on desire but negative anticipated emotions did not effect on desire. Fourth, desire had a effect on acceptance intention. [Conclusions] According to the result, sports O2O service operators should do best to improve consumers positive attitude. Especially, they have to establish marketing strategies of introducing strong aspects of sports O2O services. Also, providing easy processes and intuitive interface are needed to consumers. To promote sports O2O services to potential consumers which is unfamiliar to that services, it is important to induce easy ways for potential consumers to experience sports O2O services.